Pengaruh Kepemimpinan dan Budaya Organisasi Terhadap Organizational Citizenship Behavior Melalui Kepuasan Kerja - Saputri, Deva Aulia; Sasmita, Jumiati; Junaidi, Rahmat (Journal of Business and Economics Research (JBE), 2024)
This study aims to analyze the influence of leadership and organizational culture on Organizational Citizenship Behavior (OCB) with job satisfaction as an intervening variable among employees at PT. Agung Automall SM Amin. The research adopts a quantitative approach using a survey method, with data collected through questionnaires distributed to the employees. Data analysis was performed using path analysis and the Sobel test to examine mediation. The results indicate that leadership has a positive but insignificant effect on OCB, with a significance value of 0.757 (>0.05), while organizational culture has a positive and significant effect on OCB, with a significance value of 0.000 (<0.05). Job satisfaction also has a positive and significant effect on OCB, with a significance value of 0.000 (<0.05). The influence of leadership on job satisfaction was found to be insignificant, with a significance value of 0.709 (>0.05), while organizational culture positively and significantly affects job satisfaction, with a significance value of 0.023 (<0.05). According to the Sobel test, job satisfaction does not mediate the effect of leadership on OCB, with a probability value of 0.347 (>0.05), but it successfully mediates the effect of organizational culture on OCB, with a probability value of 0.031 (<0.05).